IMPERATIVE POLITENESS OF STUDENTS IN SMA NURUL HASANAH MEDAN - Bima Prana Chitra, Misla Geubrina (LP2M Universitas Muslim Nusantara Al Washliyah, 2021)
Sociolinguistics is a branch of linguistics that deals with language as a social and cultural phenomenon. This study focuses on the variety of utterances used by humans in interacting in social life. In interacting, humans must use polite language so that the other person feels valued and the message conveyed is also well received. Politeness connects language with social structure and behavior or ethics. The purposes of this research are to describe the form of politeness in imperative language in SMA Nurul Hasanah students in Medan and describe strategies that can be used as a marker of politeness in speech. The theory used is a sociolinguistic theory of language politeness. The method used is descriptive qualitative method and data obtained through questionnaires and observations. It can be concluded that students of grade XII SMA Nurul Hasanah Medan use imperative utterances in daily speech acts. This study uses six strategies out of eight strategies used as parameters. The six strategies include (1) use indirect speech, (2) show pessimism, (3) minimize coercion, (4) apologize, (5) use impersonal form, and (6) utter speech acts as politeness that is polite general. This strategy involves the speaker and the interlocutor in the activity.